The hotel X-Belitung marketing strategy evaluation in the Covid-19/ Mustika Permatasari, Mega Aldora and Alditya Detmuliati - Permatasari, Mustika; Aldora, Mega; Detmuliati, Alditya (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
Belitung island was one of the areas allowed by the central government to reopen the tourist sector of the Covid-19. During Covid-19, the number of living rooms in the Hotel X Belitung was still very low, even though the marketing and health protocols had already been carried out. This research took place in Hotel X as one of 4 stars hotels in Belitung. Data collection techniques are documentation, interviews, and observations. The data analysis technique is using swot analysis. This research was conducted to evaluate the marketing strategy by the Hotel X Belitung in the Covid-19 and the form of marketing strategy innovations that can be done.